A Dyadic Study on Perceived Stress and Couple Adjustment During Pregnancy: The Mediating Role of Depressive Symptoms. (November 2020) - Baldoni, Franco; Giannotti, Michele; Casu, Giulia; Luperini, Valerio; Spelzini, Federico
Stress is associated with dyadic adjustment during transition to parenthood, but little is known about mechanisms underlying this link, particularly during prenatal period. This dyadic study explored the mediating role of depressive symptoms in the relationship between perceived stress and dyadic adjustment in expectant couples. One hundred and fourteen couples at the third trimester of pregnancy completed self-reports of perceived stress, depression, and dyadic adjustment. Results indicated that both parents' perceived stress was associated with their own lower relationship satisfaction directly and indirectly, through their own higher depressive symptoms. Mothers' perceived stress was also linked to higher fathers' depressive symptoms, and thus also to lower fathers' relationship satisfaction. Both parents' perceived stress was only directly associated with their own dyadic consensus, and their own and their partners' affectional expression. Findings suggest that interventions aimed at reducing expectant parents' perceived stress could protect against depressive symptoms and promote the couple's adjustment during pregnancy.